PASAT: pathfinder in solar adaptive telescope - Rao, Changhui; Ji, Haisheng; Bao, Hua; Rao, Xuejun; Yang, Jinsheng; Guo, Youming; Zhang, Lanqiang; Zhong, Libo; Fan, Xinlong; Zhang, Qingmin; Li, Cheng; Bian, Qing (Frontiers in Astronomy and Space Sciences, 2024)
In the forefront of quantitative solar physics research using large aperture ground-based solar optical telescopes, the high contrast observation along with high accuracy polarimetric measurement in the solar active region are required. In this paper, we propose a novel high contrast imaging telescope construction with a 60 cm medium aperture, namely the PAthfinder in Solar Adaptive Telescope (PASAT), in which a deformable secondary mirror is used as the adaptive optical correction device, and a symmetrical optical path design is employed leading to the least Muller matrix polarization instruments. The telescope can provide high-resolution magnetic field with high accuracy for the solar active regions, as well as high contrast images with the superior signal-to-noise ratio and photometric accuracy of the solar photosphere and chromosphere. These data will be directly used for a better understanding, evolution and release of magnetic energy which will help to improve space weather forecasting. Meanwhile, PASAT will accumulate relevant technique for constructing similar larger solar telescope in the future.